Preferences of dermato-oncologists for adjuvant therapy in stage II melanoma: a nationwide discrete choice experiment - Kraaz, Amelie; Peitsch, Wiebke K.; Ratusznik, Laura; Diehl, Katharina; Kromer, Christian; Akbarzadeh, Dilan; Schaarschmidt, Marthe-Lisa; Weilandt, Juliane (Acta dermato-venereologica, 2025)
Adjuvant treatment decisions in stage IIB/C melanoma require careful weighing of benefits and risks. Our aim was to investigate how dermato-oncologists in Germany prioritize efficacy, toxicity, and application mode of modern adjuvants in these stages. In a nationwide discrete choice experiment physicians evaluated hypothetical treatment scenarios that varied in recurrence risk, risk of severe adverse events, type of adverse events, and mode of administration. Two patient profiles were presented, including a 55-year-old healthy patient in stage IIB (P1) and an 83-year-old patient in stage IIC with comorbidity (P2). Physicians (n = 112) preferred adjuvant therapy to the opt-out option in 86.4% of scenarios for P1 and in 60.5% for P2. The risk of severe adverse events was considered most important for both patients and significantly more relevant for P2 (relative importance score (RIS) 53.6 vs 40.2, p < 0.001), while recurrence risk was more relevant for P1 (RIS 36.3 vs 21.8, p < 0.001). Immune-related adverse events were less acceptable than gastrointestinal symptoms or pyrexia. Infusions at longer intervals were favoured compared with oral therapies. In conclusion, dermato-oncologists prioritized safety over efficacy, particularly in the older, comorbid patient. These preferences should be reconciled with patients’ preferences and treatment goals during shared decision-making.